2023
DOI: 10.1093/plcell/koad105
|View full text |Cite
|
Sign up to set email alerts
|

CycC1;1–WRKY75 complex-mediated transcriptional regulation of SOS1 controls salt stress tolerance in Arabidopsis

Abstract: SALT OVERLY SENSITIVE1 (SOS1) is a key component of plant salt tolerance. However, how SOS1 transcription is dynamically regulated in plant response to different salinity conditions remains elusive. Here, we report that C-type Cyclin1; 1 (CycC1; 1) negatively regulates salt tolerance by interfering with WRKY75-mediated transcriptional activation of SOS1 in Arabidopsis (Arabidopsis thaliana). Disruption of CycC1; 1 promotes SOS1 expression and salt tolerance in Arabidopsis because CycC1; 1 interferes with RNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…9). WRKY75 was previously described to act as a positive regulator of salt stress tolerance through activation of SOS1 expression (Lu et al 2023). Similar to previous study, we also observed wrky75 mutants to be more sensitive to salt stress within our experiments (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…9). WRKY75 was previously described to act as a positive regulator of salt stress tolerance through activation of SOS1 expression (Lu et al 2023). Similar to previous study, we also observed wrky75 mutants to be more sensitive to salt stress within our experiments (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…10A). Under 75 mM salt, only wrky75-3 showed significant reduction in main root length compared to all other genotypes tested, confirming the previously described salt sensitivity for wrky75 mutant under salt stress (Lu et al 2023). We have not observed any differences in main root length under 125 mM salt across all genotypes tested (Fig.…”
Section: Sr3g Expression Is Regulated By Wrky75 Transcription Factorsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition to its role in regulating flowering, WRKY75 is also involved in a variety of physiological processes, including leaf senescence, phosphate starvation response, and pathogen resistance (Guo et al, 2017, Chen et al, 2021, Devaiah et al, 2007). Lu et al found that salt stress induces the expression of WRKY75 in roots, and WRKY75 subsequently enhances salt tolerance by activating the expression of SOS1 , which encodes a Na + /H + antiporter that can expel excessive Na + from cells (Lu et al, 2023). In this study, we found that in shoots, WRKY75 is repressed by salt stress and leads to flowering delay.…”
Section: Discussionmentioning
confidence: 99%
“…Under salt stress, the presence of PA recruits SOS2 and MPK6 onto the PM and enhances their kinase activity to promote Na + efflux mediated by SOS1 (Yu et al, 2010; Li et al, 2023a). In addition to the post‐transcriptional regulation of SOS pathway components, many studies have investigated the transcriptional regulation of SOS genes, which was outlined well in a recent review (Ali et al, 2023) and further elucidated in recent studies (Lu et al, 2023; Ma et al, 2023a). Collectively, these studies demonstrated that the SOS pathway and its regulators play a main role in Na + export from root to soil solutions, and in salt tolerance in the shoot tissue (Quan et al, 2007).…”
Section: Physiological and Molecular Underpinnings Of Plant Responses...mentioning
confidence: 99%